The influence of early radiolucent lines appearing on femoral head penetration into HXLPE cemented sockets. Issue 4 (July 2018) - Morita, Daigo; Seki, Taisuke; Higuchi, Yoshitoshi; Takegami, Yasuhiko; Amano, Takafumi; Ishiguro, Naoki
Introduction: This study investigates differences in femoral head penetration between highly cross-linked polyethylene (HXLPE) cemented sockets both with and without radiolucent lines (RLLs) in the early postoperative phase and at 5 years follow-up. Methods: There were 35 patients (37 hips), mean age of 66.8 years, who underwent total hip arthroplasty (THA) using highly HXLPE cemented sockets. They were divided into 2 groups based on postoperative the early appearance of RLLs. Femoral head penetrations on both anteroposterior- and Lauenstein-view radiographs were evaluated, and the mean polyethylene (PE) wear rate was calculated based on femoral head penetrations between 2 and 5 years. Results: Femoral head penetrations in the proximal direction were 0.075 mm and 0.150 mm in the RLL and non-RLL groups at 1 year postoperatively ( p = 0.019). At 5 years measured penetration was 0.107 mm and 0.125 mm in the RLL and non-RLL groups, respectively ( p = 0.320). The mean PE wear rates in anteroposterior-view were 0.008 mm/year and 0.003 mm/year in the RLL and non-RLL groups ( p = 0.390) and those in Lauenstein-view were 0.010 mm/year and 0.005 mm/year, respectively ( p = 0.239). Conclusions: In the RLL group, the PE bedding-in was less compared with those in the non-RLL group. Additionally, the mean PE wear rate in the RLL group tended to be higher than that in the non-RLL group. The distribution of stress loading through the cement may differ according to whether early RLLs appear.